Pengaruh Shot Peening terhadap Laju Perambatan Retak Fatik Sambungan Friction Stir Welding pada Aluminium Seri 5083 - Wartono Wartono (Jurnal Engine: Energi, Manufaktur, dan Material, 2020)
This research aims to find out the effect of shot peening on the rate of fatigue crack propagation in the aluminum alloy 5083, which has undergone the friction stir welding (FSW) process. In general, the FSW welded joint is subjected to softening and decreasing mechanical properties compared to the parent metal. Shot peening treatment is expected to reduce the rate of fatigue crack propagation. The FSW process is carried out on 3 mm thick aluminum and butt joint welding joints. The machine used in the FSW process is a milling machine with a spindle rotation of 910 rpm and a table speed of 18.2 mm/min. The surface of the material that has been processed by FSW, then proceeds with the shot peening process by firing steel balls for 6 minutes, 10 minutes, and 14 minutes. The results of the FSW process without shot peening (NP) and FSW with shot peening (SP) microstructure, SEM, and fatigue crack propagation tests were performed. The test results show that the FSW process with shot peening has decreased the rate of fatigue crack propagation marked by an increase in the value of the Paris constant (n). The increase in Paris's constant values (n) in the FSW with SP6, SP10, and SP14 was 0.241%, 5.428%, and 13.371%, respectively.